A colorimetric hydroxy naphthol blue based loop-mediated isothermal amplification detection assay targeting the β-tubulin locus of Sarocladium oryzae infecting rice seed - Logeshwari, R.; Gopalakrishnan, C.; Kamalakannan, A.; Ramalingam, J.; Saraswathi, R. (Frontiers in Plant Science, 2022)
One of the most significant rice seed-borne pathogens, S. oryzae causes serious yield losses. The detection and diagnosis of pathogens in rice seeds is crucial to ensure disease-free seeds and curtail subsequent production losses. Traditionally, blotter tests are exploited to assess the incidence of infection in seed lots and require incubation for up to one week. Molecular diagnosis of seed pathogens can promote food security by facilitating the quick detection of potentially destructive seed pathogens and offering indispensable insights for disease management strategies to be implemented. However, PCR-based assays require sophisticated laboratories and equipment, which is not amenable to on-site detection of seed-borne pathogens. Loop-mediated isothermal amplification (LAMP) is ideal for field-level diagnosis since it offers quick, high-specific amplification of target template sequences at a single temperature. We designed primers based on the β-tubulin region of S. oryzae. The LAMP technique devised was extremely sensitive, detecting the presence of the S. oryzae template at concentrations as low as 10 fg in 30 minutes at 65 °C. The assay specificity was confirmed by performing the experiment with genomic DNA isolated from 22 different phytopathogens. Through the addition of hydroxy naphthol blue in the reaction process prior to amplification, a colour shift from violet to deep sky blue was seen in the vicinity of the target pathogen only. Finally, the LAMP assay was validated using live infected tissues, weeds and different varieties of seeds collected from different locations in Tamil Nadu. The LAMP assay developed has the potential applications in seed health laboratories, plant quarantine stations and on-site diagnosis of S. oryzae in seeds as well as in plants.